Land Asset Securitization : An Innovative Approach to Distinguish between Benefit-sharing and Compensation in Hydropower Development - Shi, Guoqing; Shang, Kai (Taylor and Francis, 2022)
Development Project (DP) is creating the benefits for all and taking benefit-sharing (BS) as a goal. BS involves paying something above the fair market compensation or replacement value of the assets lost in the displacement and resettlement. BS becomes more important and complicated when the lost assets are not transacted as commodities in a market. BS is a key to resolve the challenges on impoverishment caused development induced displacement and resettlement globally. An innovated BS approach and methodology for land asset securitization (LAS) is proposed. It takes occupied lands as capital investment in the DP rather than for displaced assets’ compensation only based on natural resources transfer theory. LAS takes the approach in lands resourcing, land resources capitalization and land assets securitization. It establishes the mechanism to arrange additional benefits for resettlers. It enables rural resettlers to receive appropriate compensation to sustain basic livelihoods at the DP construction and early commercial operation stage as well as share profits equally during full operation. LAS will prevent either the hydropower developer or the government from having interests in securitized assets. LAS is a sustainable approach to promote win-win among resettlers, developers, governments, and civil society.